Effects of Aggregate Size on Concrete Tensile Strength - Muktar, Mohd Amin (Universiti Teknologi Petronas, 2007)
Concrete properties are dependant on many factors and one of them is the aggregate. ' Aggregates play a major role to the concrete properties as it present most of the concrete volume, Aggregate can affects both fresh and hardened concrete properties. Some of the major aggregate properties that influenced concrete structures are the size, particle shape, surface texture, bulk density and its water absorption. In this project, concrete mix was design by using one particular size of coarse aggregate and the tensile strength was determined. It is understood that the tensile strength came from the strength of the cement paste to hold the aggregates. By introducing the same and smaller size of aggregates, more surface area for the cement paste to contact are provided. Other factors affecting concrete tensile strength are porosity, water cement ratio and the cement that being used in the concrete.